ANALYSIS OF INDONESIA'S NATURAL RUBBER COMMODITY EXPORTS TO THE 5 MAIN DESTINATION COUNTRIES FROM AN ISLAMIC ECONOMIC PERSPECTIVE YEAR 2016-2025 - Arrohmanza, Arrohmanza; Bahtiar, M. Yusuf; Ermawati, Liya (Ad Deenar: Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to analyze the influence of natural rubber production variables, world rubber prices, and exchange rates (exchange rates) on the value of Indonesia's rubber exports in the 2016-2025 period from an Islamic economic perspective. Indonesia is the world's main producer of rubber, but global price fluctuations and exchange rate instability pose a significant challenge to the welfare of farmers and the country's foreign exchange. The research method used was quantitative with a multiple linear regression model using the EViews 10 software device. The results of the study show that partially, the variables of natural rubber production (X1) and international rubber prices (X2) have a positive and significant effect on the export value (Y). In contrast, the exchange rate variable (X3) did not have a significant influence on the value of rubber exports in that period. Simultaneously, the three independent variables had a significant effect on the export value with the ability to explain the data variation (Adjusted R Square) of 87.8%. From the perspective of Islamic economics, these findings indicate the dominance of the real sector (production) over the monetary sector, which is in line with the principles of maslahah (benefit) and distributive justice for smallholders through a transparent pricing mechanism (thaman al-mithl) without the element of speculation (gharar).